Pemetaan Pelanggan IndiHome Sebagai Daerah Sasaran Promosi (Studi Kasus : Witel Bandung) - Nisa Hanum Harani; Cahyo Prianto; Andri Fajar Sunandhar (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2020)
In this globalization era, marketing communication is very important to help increase sales promotion of indihome digital service products by utilizing customer location points that use indihome services. Currently there are many information systems that are used to support and solve problems in determining the location of a place. Determination of location can be done using mapping. The mapping of Indihome customers is done by utilizing a map provided by Google, the Google Maps API based on the address of the Indihome service customer. Therefore, we need a system to find out which areas use the most indihome services, so that it will make it easier to target promotions for indihome customers who have not used to add services to Indihome such as Movin, Indihome Gamers, Indihome Music, Indihome Music, Indihome Studies, Indihome Storage, Indihome Servers, Video Calls, and other additional packages. The results of this mapping can determine areas / regions that have the potential to be promoted in connection with the addition of indihome service products, so that it will have an impact on increasing customers and sales revenue of Add On products.